Permeation of styryl dyes through nanometer-scale pores in membranes. - Wu, Y; Ma, L; Cheley, S; Bayley, H; Cui, Q; Chapman, E (2011)
Styryl dyes are widely used to study synaptic vesicle (SV) recycling in neurons; vesicles are loaded with dye during endocytosis, and dye is subsequently released via exocytosis. During putative kiss-and-run exocytosis, efflux of dye from individual SVs has been proposed to occur via two sequential steps: dissociation from the membrane followed by permeation through a small fusion pore. To improve our understanding of the kinetics of efflux of dye from vesicles during kiss-and-run events, we examined the rates of efflux of different dyes through nanometer-scale pores formed in membranes by the toxins melittin and α-hemolysin; these pores approximate the size of fusion pores measured in neuroendocrine cells. We found that the axial diameter of each dye was a crucial determinant for permeation. Moreover, the two dyes with the largest cross-sectional areas were completely unable to pass through pores formed by a mutant α-hemolysin that has a slightly smaller pore than the wild-type toxin. The overall time constant for efflux (seconds) of each dye was orders of magnitude slower than the time constant for dissociation from membranes (milliseconds). Thus, the permeation step is rate-limiting, and this observation was further supported by atomistic molecular dynamics simulations. Together, the data reported here help provide a framework for interpreting dye destaining rates from secretory vesicles.